A quantification control method of electromagnetic environmental effects for complex systems. Issue 2 (22nd January 2021) - Tang, Shiping; Mao, Junfa
ABSTRACT: Modern aircraft, ship, and other systems have different consequences when faced with the own and external radio frequency, lightning and other electromagnetic environments (EME) radiation, that is called electromagnetic environmental effects (E3). In this paper, a new method of system-level E3 quantitative control is proposed. A two factor E3 impact degree model composed of susceptible receptor importance and consequence severity is established. The selection and calculation method of relevant parameters is given. The application process of this method is illustrated with examples of high intensity radiated fields (HIRF), lightning, electromagnetic interference (EMI) and radiation hazard elements for aircraft. It is proved that this method can quantitatively, clearly and accurately express the impact degree of E3, balance the conflict of multi-index and multi-objective design, and achieve the engineering optimization when solving the whole system, whole element and whole process E3 control problems.